Sistem Informasi Geografis analisis kebiasaan merokok warga Indonesia ≥ 15 tahun (2020-2022) - Rizqi pasha eko adi prabowo; Bambang agus herlambang; Ahmad khoirul anam (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Smoking is a high-risk habit for health, which is difficult to give up in Indonesia due to the large number of smokers and the general prevalence of smoking. Even though the age limit for cigarette consumption has been set, there are still children aged 15 years who are involved in smoking. Therefore, this study proposes the use of a Geographic Information System to map the Web-Based Percentage of Smoking in Population Aged ≥ 15 Years in Indonesia, by utilizing Quantum GIS software as a smoking prevalence survey tool. The method used in this research is the GIS Development Guide Method. Using this method, the research will collect smoking prevalence data from 34 provinces in Indonesia to identify different smoking patterns in certain regions.